2015
DOI: 10.1088/0004-6256/149/2/59
|View full text |Cite
|
Sign up to set email alerts
|

THE CHEMICAL COMPOSITION OFρPUPPIS AND THE SIGNS OF ACCRETION IN THE ATMOSPHERES OF B–F-TYPE STARS

Abstract: We investigated the chemical composition of ρ Pup using high-resolution spectral observations taken from the Very Large Telescope and the IUE archives and also spectra obtained at the 1.8 m telescope of the Bohyunsan observatory in Korea. The abundances of 56 chemical elements and the upper limits of Li and Be abundances were determined. The abundance pattern of ρ Pup was found to be similar to that of Am-type stars. The possibility of the influence of the accretion of interstellar gas and dust on the abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 82 publications
6
39
0
Order By: Relevance
“…As shown by Yushchenko et al (2015, Fig. 7), this correlation is positive for the groups of stars with effective temperatures in the range of 7,000-12,000 K, and negative for groups of stars with lower temperatures, specifically in the 5,900-7,000 K range.…”
Section: δLognmentioning
confidence: 72%
See 3 more Smart Citations
“…As shown by Yushchenko et al (2015, Fig. 7), this correlation is positive for the groups of stars with effective temperatures in the range of 7,000-12,000 K, and negative for groups of stars with lower temperatures, specifically in the 5,900-7,000 K range.…”
Section: δLognmentioning
confidence: 72%
“…Unfortunately, this hypothesis is not fully developed yet. Recently, Yushchenko et al (2015) made a review devoted to this problem, and found some new possible observational confirmations. One of them is the correlation -667 (circles) with the solar system r-process abundance distribution (Simmerer et al 2004) scaled at the observed Gd abundance (line).…”
Section: All Chemical Elements In the Atmosphere Of Rm_1-390mentioning
confidence: 98%
See 2 more Smart Citations
“…Spectroscopic analysis of 56 chemical elements in pulsating δ Sct stars ρ Pup and δ Sct itself (Yushchenko et al 2015) revealed a correlation between relative abundances of elements versus the second ionization potentials, having discontinuities at 13.6 and 24.6 eV -the ionization potentials of hydrogen and helium, respectively. These correlations have been explained as accretion of interstellar gas onto the stellar atmosphere.…”
Section: Main Sequence A-f Starsmentioning
confidence: 99%